Analysis of Service Differentiation Strategies in Integrated Islamic Schools in Semi-Urban Areas: Analisis Strategi Diferensiasi Layanan Pendidikan pada Sekolah Islam Terpadu di Wilayah Semi Kota - Ripai, Iip; Khusni, Khusni; Jakiyah, Paridah (Medpro, 2025)
This study aims to analyze the forms, effectiveness, and challenges of service differentiation strategies implemented by SMP IT Al-Muhsinin Integrated Islamic Junior High School, located in a semi-urban area. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation studies. The findings reveal that SMP IT Al-Muhsinin applies differentiation strategies through the integration of national and Islamic curricula, a humanistic learning approach, contextual extracurricular activities based on Islamic values, and responsive administrative services. These strategies have been proven to increase public trust and student enrollment, while also shaping a positive image as a modern Islamic educational institution. Nevertheless, their implementation faces several challenges, including limited facilities, disparities in teachers’ competencies, and the diverse social backgrounds of the community. This study recommends strengthening infrastructure, enhancing teacher capacity, and developing adaptive educational communication strategies aligned with the local context as steps for further improvement.